Вибір та розробка crm-систем для бізнесу: ключові фактори та етапи реалізації - Захарова, Л. М.; Назаров, О. С. (ХНУРЕ, 2025)
This article explores the main functions of CRM systems, as well as approaches to choosing between implementing ready-made solutions and developing custom CRM systems for businesses. ІТ provides a comprehensive analysis of the processes involved in selecting the optimal CRM system for specific business needs. The study covers key factors that determine the effectiveness of CRM systems, as well as the stages of their development and implementation. ІТ has been established that the choice between ready-made and custom solutions depends on business requirements, company size, and available resources. The article emphasizes the importance of the right approach to CRM system implementation for optimizing business process management.
Keywords: crm-система; бізнес